Modeling and mu-synthesis control of a flexible rotor stabilized by active magnetic bearings including current free control. (3rd March 2023) - Hutterer, Markus; Schrödl, Manfred
Abstract: Designing a controller for a magnetically stabilized rotor that experiences non negligible gyroscopic moments requires careful attention on the rotordynamic behavior, the design of the position and current free control as well as the actuator and sensor characteristics. Most of the controller design procedures for magnetic bearings separate the synthesis of the current free controller and the position controller using different methods. This article connects the synthesis of the current free controller and the position controller in the μ -framework. Therefore, the modeling of the rotor, the position controller design and the design of the current free control of a flexible rotor stabilized by active magnetic bearings is described. The rotor is modeled by using the finite element method. Afterwards, the flexible system is reduced to get an appropriate model size for the control design. For the optimization of the controller parameters the μ -synthesis method is applied. However, compared to the general μ -synthesis method in this article an a priori fixed control structure is utilized. This control structure splits up the tilting subsystem to a control path for the nutation mode and one for the precession mode. Thus, the proposed controller has the advantage of a low system order and that the parameter variant nature of the plant is already considered in the control structure. Additionally, the synthesis of the current free controller is added to the μ -framework. Hence, the current free controller is optimized for a plant with defined uncertainties using necessary constraints of the closed loop systems. Finally, the stabilization of the system using the proposed control method is experimentally validated on a turbomolecular pump with a magnetically levitated rotor. Highlights: μ -synthesis control of a magnetically stabilized flexible rotor. Robust current free control of active magnetic bearings. Inclusion of the current free controller in the μ -framework. Usage of a fixed order cross coupled controller for the optimization. Decoupling of the nutation and precession movements.